Planning for Sustainability : Creating Livable, Equitable and Ecological Communities. - Wheeler, Stephen M., 1957- (Taylor and Francis, 2013)
How can human communities sustain a long-term existence on a small planet? This challenge grows ever more urgent as the threat of global warming increases. Planning for Sustainability presents a wide-ranging, intellectually well-grounded and accessible introduction to the concept of planning for more sustainable and livable communities. The text explores topics such as how more compact and walkable cities and towns might be created, how local ecosystems can be restored, how social inequalities might be reduced, how greenhouse gas emissions might be lowered, and how more.